Smoking gun : the true story of gunfighting in the Old West - Agnew, Jeremy (Lake City, CO : Western Reflections Publishing, 2010)
For more than a century, stories about gunfighters and gunfighting in America s Wild West have captivated the imaginations of millions of people worldwide. In his book, Smoking Gun the True Story about Gunfighting in the Old West, Jeremy Agnew gives readers a different perspective skillfully separating fact from exaggeration and providing believability and proof that fact can many times be stranger (and more interesting) than fiction. In this well-researched and documented work, Agnew takes a look at what really made the gunfighter tick and why the era of gunfighting occurred when it did from 1865 to 1900. Combining data on the evolution of firearms, the methods of using those tools of the trade, and circumstances that contributed to the shoot-em-up environment of the time, this book details who the gunfighter was, how he became a symbol of the West, and what made some towns the baddest of the bad. From the casual to the most ardent reader of Old West history, this book promises to be new, interesting and absorbing.
Includes Index and Bibliography
Keywords: Gunfights -- West (U.S.) -- History; Outlaws -- West (U.S.); Peace officers -- West (U.S.); Frontier and pioneer life -- West (U.S.); West (U.S.)